Answer:
B
Step-by-step explanation:
Answer: 22
Step-by-step explanation:
To get from 59 to 51 you subtract 8 then it was minus 7, then minus 6, then minus 5, and then it just kept going down like that
9514 1404 393
Answer:
25 (ft/s)
Step-by-step explanation:
The "rate of change" is taken to mean the "rise" divided by the "run". Here, adjacent points differ in their y-value by 25 ft and their x-value by 1 second.
The rate of change is ...
rise/run = (25 ft)/(1 second) = 25 ft/second
Usually, we're just interested in the numerical value: 25.
_____
<em>Additional comment</em>
The graph is mis-labeled. It is not showing "rate of ascent." It is showing height as a function of time. The "rate of ascent" is the <em>slope</em> of the line on the graph, not its <em>value</em>.
Answer:
![\large \boxed{12}](https://tex.z-dn.net/?f=%5Clarge%20%5Cboxed%7B12%7D)
Step-by-step explanation:
We can apply Pythagoras' Theorem.
![\begin{array}{rcc}a^{2} & = & b^{2} + c^{2}\\13^{2}& = & 5^{2} + c^{2}\\169& = & 25 + c^{2}\\c^{2}& = & 144\\c & = & \sqrt{144}\\& = & \mathbf{12}\\\end{array}\\\text{The other leg of the triangle is $\large \boxed{\mathbf{12}}$}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Brcc%7Da%5E%7B2%7D%20%26%20%3D%20%26%20b%5E%7B2%7D%20%2B%20c%5E%7B2%7D%5C%5C13%5E%7B2%7D%26%20%3D%20%26%205%5E%7B2%7D%20%2B%20c%5E%7B2%7D%5C%5C169%26%20%3D%20%26%2025%20%2B%20c%5E%7B2%7D%5C%5Cc%5E%7B2%7D%26%20%3D%20%26%20144%5C%5Cc%20%26%20%3D%20%26%20%5Csqrt%7B144%7D%5C%5C%26%20%3D%20%26%20%5Cmathbf%7B12%7D%5C%5C%5Cend%7Barray%7D%5C%5C%5Ctext%7BThe%20other%20leg%20of%20the%20triangle%20is%20%24%5Clarge%20%5Cboxed%7B%5Cmathbf%7B12%7D%7D%24%7D)
Please, use parentheses to enclose each fraction:
y=3/4X+5 should be written as <span>y=(3/4)X+5
Let's eliminate the fraction 3/4 by multiplying the above equation through by 4:
4[y] = 4[(3/4)x + 5]
Then 4y = 3x + 20
(no fraction here)
Let 's now solve the system
4y=3x + 20
4x-3y=-1
We are to solve this system using subtraction. To accomplish this, multiply the first equation by 3 and the second equation by 4. Here's what happens:
12y = 9x + 60 (first equation)
16x-12y = -4, or -12y = -4 - 16x (second equation)
Then we have
12y = 9x + 60
-12y =-16x - 4
If we add here, 12y-12y becomes zero and we then have 0 = -7x + 56.
Solving this for x: 7x = 56; x=8
We were given equations
</span><span>y=3/4X+5
4x-3y=-1
We can subst. x=8 into either of these eqn's to find y. Let's try the first one:
y = (3/4)(8)+5 = 6+5=11
Then x=8 and y=11.
You should check this result. Subst. x=8 and y=11 into the second given equation. Is this equation now true?</span>